Creatine supplementation and its influence on human organism - Siedlecki, Wojciech; Remjasz, Klaudia; Kosz, Katarzyna; Kuchnicka, Aleksandra; Kuchnicka, Julia; Zarankiewicz, Natalia; Zielińska, Martyna; Sapuła, Klaudia; Aleksandrowicz, Jakub; Fabiś, Mateusz (Journal of Education, Health and Sport, 2022)
Background: Creatine supplementation is one of the most popular methods of improving athletic performance. In this article we reviewed its positive and negative influence on human organism. Materials and Methods: This paper was based on medical articles collected in PubMed from 1998 to 2019. The research has been done by looking through the key words such as: “creatine”, “supplementation”, “influence”, “kidney”, “renal effects”. Results: Creatine supplementation has no negative influence on renal function. Moreover it appears to have a positive effect on some aspects of metabolism. Conclusions: According to the available knowledge, creatine supplementation in appropriate doses is safe.